New insights into the enzymatic hydrolysis of lignocellulosic polymers by using fluorescent tagged carbohydrate-binding modules. Issue 2 (21st December 2017) - Khatri, Vinay; Meddeb-Mouelhi, Fatma; Beauregard, Marc
Abstract : Modification of lignocellulosic polymers at the surface of wood fibers can easily be monitored using fluorescent probes (FTCM method). By applying FTCM, a simple and rapid method, biomass industries could substantially improve cost-effectiveness of production of biofuels and other lignocellulosic biomass-based products. Abstract : The development of a bio-based economy requires the utilization of lignocellulosic biomass in a cost-effective way. The economic viability of lignocellulosic biomass-based industries is hindered by our imperfect understanding of biomass structure and suboptimal industrial processes. To achieve such goals requires direct and rapid monitoring of lignocellulosic polymers as they are physically, chemically, and/or enzymatically treated. In this study, the recently reported fluorescent protein tagged carbohydrate binding modules method (FTCM) was used to specifically track mechanical, chemical and enzymatic-induced variations of hemicelluloses at the surface of different wood fibers. Our results showed that susceptibility to hydrolysis in kraft pulp was higher for xylan, while mannan was more vulnerable in mechanical pulps. Furthermore, FTCM rapidly and efficiently detected enzymatic inactivation and the apparent complementarity (additive and/or synergistic effect) between cellulase and other enzymes (xylanase and mannanase), significantly bolstering cellulose and hemicelluloses hydrolysis. Subsequent addition of xylanase and mannanase enzymes directly proved that xylan was acting as a physical shield which was covering mannan in bleached kraft pulp. This study suggests that mannan was closely associated with cellulose or was deeply embedded in the cell wall organization of such fibers. FTCM provided direct support for previous models on fiber structure that were based on time-consuming and complicated approaches ( i.e. chromatography, spectroscopy and microscopy). FTCM allowed for the monitoring of layers of polymers as they were exposed after treatments, providing key information regarding hydrolysis optimization and the specific susceptibility of xylan and mannan to biomass treatments. We believe that by applying this simple and rapid method on site, biomass industries could substantially improve cost-effectiveness of production of biofuels and other lignocellulosic biomass-based products.